Climate change and disease risk in the Himalayas - Sarkar, Sahotra (Himalayan Journal of Sciences, 2011)
A new challenge is unfolding in the Himalayas: a significant increase in the burden of infectious disease, driven by climate change. Vectors are moving beyond their historic ranges to higher elevations; water quality is deteriorating, and the available supply is diminishing. Preventive and ameliorative measures to address these problems require robust quantitative estimates of the size and spatial distribution of disease risk. Once enough data are available, disease risk can be mapped with predictive models so that appropriate policies can be formulated and implemented. Unfortunately, there has been virtually no quantitative epidemiological attention to this region. DOI: http://dx.doi.org/10.3126/hjs.v6i8.4921 Himalayan Journal of Sciences Vol.6 Issue 8 2010 pp.7-8